Current views on etiology of alopecia areata - Joss-Wichman, Ewa; Broniarczyk-Dyła, Grażyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Alopecia areata (AA) is a common disease of the skin, constituting about 2% of all dermatoses. It occurs in humans, but also other mammals and may develop at any age. The disease can present with two main forms – AA vulgaris (AAV) and AA totalis /universalis (AAT/U). Current views on etiology of this condition are presented in the paper. On the base of modern literature the most popular etiological theories, explaining the pathomechanism of hair loss, are discussed. These include autoimmune, immunologic and genetic theory, as well as involvement of the disturbances in the apoptosis process. Psychogenic factors may also have a role in etiology of the disease, what can be associated with action of neuromediators released in vicinity of the hair follicle. alopecia areata still belongs to the diseases that pose significant therapeutic difficulties in clinical practice.